The new encyclopedia of Islam - Glassé, Cyril; Smith, Huston; Glassé, Cyril (Walnut Creek, CA : AltaMira Press, 2001)
This encyclopedia comprehensively encompasses the beliefs, practices, history and culture of the Islamic world, in over 1300 entries. It has the further unique advantage of being written by a Western scholar of the Islamic faith, and has thus been already widely praised for straddling the cultures with an understanding and respect for the themes and topics covered. All aspects of religious belief, ritual, practices, prayer, significant political movements, spiritual and political leaders, art, architecture, sects, law, social institutions, history, ethnography, nations and states, languages, science, major cities and centers of learning are covered.
"Revised edition of the Concise encyclopedia of Islam."
Includes bibliographical references (p. 530-534).
Keywords: Islam -- Dictionaries